Accessibility of Web-based information resources for people with disabilities - Schmetzke, Axel (Library hi tech, 2002)
To a large extent, disability is a social construct. Whether individuals with ''disabilities'' canpursue independent and fulfilling lives is amatter no so much of their particular internalconditions as of enabling or disabling externalfactors put in place by society.